Jejulea byssolomoides gen. et sp. nov., a Remarkable Pilocarpaceae (Lichen-Forming Ascomycetes) from Jeju Island, South Korea - Josef P. Halda; Jung-Jae Woo; Dong Liu; Soon-Ok Oh; Yogesh Joshi; Jae-Seoun Hur (Mycobiology, 2022)
The new genus and species, Jejulea byssolomoides, is described from Jeju Island, Korea. This lichen is characterized by saxicolous, crustose, pale greenish-gray, partly finely filamentous, matt, smooth thallus, prominent convex brown to dark brown ascomata with a concolorous margin constricted at the dark brown base, 300–800 μm diameter, 200–250 μm high, without a distinct proper margin, adhering to the substratum ending in a minute byssoid white external part of cylindrical cells, fusiform 3–5 septate ascospores (17–23 × 4–5 μm). Phylogenetic analyses using ITS and mtSSU sequences place Jejulea in the Pilocarpaceae (Lecanorales). The new taxon is closely related to Byssoloma, a cosmopolitan group of foliicolous lichens, which is most diverse in the tropics. Like Byssoloma, Jejulea also forms a byssoid apothecial margin.